Cherubism - Anjum Farooqui; Yogita Khalekar; Jamebashher Farooqui; Amit Zope (Wolters Kluwer Medknow Publications, 2017)
Cherubism is a rare non-neoplastic fibro-osseous disorder characterized by clinically evident bilateral painless enlargement of the jaws that usually gives a cherubic appearance. Cherubism is due to dominant mutations in the SH3-binding protein 2 (SH3BP2) gene on chromosome 4p16.3.The skeletal deformity causes dental complications. Bilateral swelling of the jaws usually appears between the age of 2 and 7 years, after which, the lesions proliferate and increase in size until puberty. These lesions subsequently begin to regress, fill with bone and remodel until the age of 30 years. Here we present a case of 20 years male patient with cherubism.